The impact of the integration process on the emergence of BRICS - Кошелєва, Христина (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 1970)
This article studies world integration processes and itsinfluence on the emergence of BRICS association. Its members Brazil, Russia, India, China and South Africa are the five countries located on three continents, with significant influence both in the region and around the world, and together they have at their disposal a large number of important for the world economy of natural resources